(untitled) (Sciences & Technology. A, exactes sciences, 2007)
First of all, we point out in this paper, the Fourier-Parseval Kernels méthod. Then we apply this technique in order to study a class of kernels for wich the Poisson Wallis and Euler’s integrals are particular cases. Thus, remarkable properties and identities are established